ORIGIN OF LIFE UNRAVELLED - Rao, Y. V. Subba; Rao, Y. V. Ramana (International Journal of Research -GRANTHAALAYAH, 2023)
A clear meaning of "Life" is even more important for these two than the "Origin of Life," which is crucial to "Evolution" itself as an emergent property of matter where biology transcends computation. The idea of panspermia as a metaphysical proposition is in fact a scientific reality when one considers ‘Jyotish’ (Vedic Astrology). In the present study, it is established that the rationale behind the subject of Jyotish (A Vedānga) is astronomy, and its life side is astrobiology, the study of how electromagnetism interacts with matter to describe “life” as an emergent property of matter. The current study of panspermia focuses on the two most important aspects of advanced complex life on earth: the Cambrian explosion and the emergence of an even more complex and intricate human brain which refutes Darwin’s Theory of Evolution and Natural Selection. Solar disturbances and their particle emissions are the most likely link between biological and extra-terrestrial events in both the Origin and Evolution of Life.